Going Beyond the Theory/Practice Divide in Early Childhood Education : Introducing an Intra-Active Pedagogy. - Taguchi, Hillevi Lenz (Contesting early childhood., 2009)
This book identifies the gaps needing to be bridged to achieve a more inclusive and?just? early childhood education, in relation to class, gender, sexuality, ethnicity, race, disabilities and age, and explores various ways of bridging these gaps.